Aminoacyl‐tRNA synthetases in medicine and disease - Peng Yao; Paul L. Fox (EMBO Molecular Medicine)
Abstract Aminoacyl‐tRNA synthetases (ARSs) are essential and ubiquitous ‘house‐keeping’ enzymes responsible for charging amino acids to their cognate tRNAs and providing the substrates for global protein synthesis. Recent studies have revealed a role of multiple ARSs in pathology, and their potential use as pharmacological targets and therapeutic reagents. The ongoing discovery of genetic mutations in human ARSs is increasing exponentially and can be considered an important determinant of disease etiology. Several chemical compounds target bacterial, fungal and human ARSs as antibiotics or disease‐targeting medicines. Remarkably, ongoing exploration of noncanonical functions of ARSs has shown important contributions to control of angiogenesis, inflammation, tumourigenesis and other important physiopathological processes. Here, we summarize the roles of ARSs in human diseases and medicine, focusing on the most recent and exciting discoveries.